2013
DOI: 10.1111/trf.12431
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen as a therapeutic target for bleeding: a review of critical levels and replacement therapy

Abstract: Fibrinogen plays a critical role in achieving and maintaining hemostasis and is fundamental to effective clot formation. There is increasing awareness of the important role of fibrinogen as a key target for the treatment and prevention of acquired bleeding. Fibrinogen is the first coagulation factor to fall to critically low levels (<1.0 g/L) during major hemorrhage (normal plasma fibrinogen levels range from 2.0 to 4.5 g/L), and current guidelines recommend maintaining the plasma fibrinogen level above 1.5 g/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
192
0
11

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(205 citation statements)
references
References 131 publications
(252 reference statements)
2
192
0
11
Order By: Relevance
“…37 These results and others from previous RCTs of fibrinogen concentrate in surgery summarized by Levy et al 38 do not highlight any thrombotic or safety concerns with fibrinogen concentrate. Further safety and adverse event data should become available for cryoprecipitate and fibrinogen concentrate with increased clinical experience and trials of fibrinogen replacement in active hemorrhage.…”
Section: Thrombotic Complicationssupporting
confidence: 55%
“…37 These results and others from previous RCTs of fibrinogen concentrate in surgery summarized by Levy et al 38 do not highlight any thrombotic or safety concerns with fibrinogen concentrate. Further safety and adverse event data should become available for cryoprecipitate and fibrinogen concentrate with increased clinical experience and trials of fibrinogen replacement in active hemorrhage.…”
Section: Thrombotic Complicationssupporting
confidence: 55%
“…There have been a number of reports on the relationship between the test results obtained by viscoelastic devices and outcome in trauma patients [28][29][30][31]. One study reported that mortality was 100% in patients manifesting fulminant hyperfibrinolysis with a mean injury severity score (ISS) of The lower right window shows a graph presenting the time course of thrombus formation in which the horizontal axis is time and the vertical axis is the measured pressure.…”
Section: Reports On the Relationship Between The Use Of Viscoelastic mentioning
confidence: 99%
“…45 Because FFP is associated with a significant number of side effects (Table 4), in particular transfusion-related acute lung injury, 55 recent studies have explored the possibility of using empirical fibrinogen concentrate or cryoprecipitate to replace FFP in critical bleeding. 56,57 Indeed, plasma fibrinogen concentration appears to be first coagulation factor to be depleted in trauma-acquired coagulopathy. 58 RCTs on early use of fibrinogen concentrate (60-70 mg/kg) in trauma-or surgery-induced hemorrhage are already under way, 59,60 and if the results are positive, a reduction in the usage of FFP in critical bleeding is anticipated.…”
Section: Benefits and Risks Of Ffp Transfusions In The Critically Illmentioning
confidence: 99%